The problem of field relationship cultural and visual anthropology in the logic of the crisis of text-centered methods of cultural research - O. Y. Pavlova, (Ukrainian Cultural Studies, 2021)
The article is devoted to the study of the relevance of anthropological issues in the beginning of twentieth century and socio-cultural background of the anthropological sciences. The specificity of the subject and method of anthropology as a science in general focused on the systematization of empirical material which was studied. In this context, the logic of the formation of cultural / social anthropology and its instrumental interest to the video productions of technical media is studied. Anthropology tried to form a scientific understanding of human world as a holistic phenomenon (combining theoretical generalizations based on empirical data), while cultural anthropology focused on the study of cultural diversity. Visual anthropology emerged as a crossing of the fields of cultural anthropology as an academic discipline and the field of application of technical optical media, and thus a new source of empirical material. The gradual accumulation of empirical material in the "field researches" of anthropologists allowed to significantly expand the subject area and optics of anthropological science. And also it allowed visual anthropology to go gradually beyond the instrumental function that was originally intended for it. Meanwhile, the text-centered view of ethnographic material led to the transform of the culture of indigenous peoples into the codes of Western civilization, and hence to its reduction. Any of the various authentic non-Western cultures fundamentally distinguishes them from the unification style of the modern culture. The accumulation of video production by ethnography has allowed not only to preserve the disappearing authentic cultures, but also to develop methods of systematization of visual material, as well as to understand the role of visual anthropology as an autonomous discipline of the humanities. The integration of two aspects of visual anthropology (the production and study of images) casts doubt the classical style of positivist science: in particular, on the one hand the status of the subject as an observer or a spectator, on the one hand, and the monopoly of text optics, on the other.
Keywords: anthropology, cultural anthropology, visual anthropology, text-centrism, text-centered view of ethnography, discourse-centered methods of cultural research